Effect of Income Inequality on the Economic Growth of Nigeria - Vivian C. Onyejegbu; Anastesia Uzonna Ezewulu (Siber International Journal of Digital Business (SIJDB), 2026)
The study focused on a well-developed econometric framework to examine how income inequality impacts economic growth in Nigeria based on annual data of 1994-2023. Linear and Autoregressive Distributed Lag (ARDL) estimation methods were used to estimate the model to include the short and long-run dynamics. The ARDL bounds test was used to ensure that there was cointegration and the error correction model (ECM) ensured that it made adjustments towards a long-run equilibrium. The theoretical and empirical relevance of the inclusion of the variables in the study justified it, and the flexibility of ARDL was adopted because of the ability to deal with mixed order of integration. FMOLS estimation was done to ensure robustness and pre-estimation tests (ADF, multicollinearity, descriptive statistics) and post-estimation diagnostics (autocorrelation, heteroskedasticity and stability tests) demonstrated model validity and reliability. The findings revealed that income inequality positively, though statistically insignificantly influenced economic growth in Nigeria thus no long-run effect. Institutional quality and population growth had a strong and positive impact on growth, whereas the combination of the two with inequality was negative and significant, indicating that good institutions mitigate the negative impact of inequality. Inequality in the short-run was insignificant and on the other hand, institutional quality and population growth were a major contributor to growth. There were mixed effects of trade openness and life expectancy and the error correction term proved that there is a high long-run adjustment. The research found that the income inequality, in itself, is not a large factor of economic growth in Nigeria, but the impact is influenced by the quality of the institutions. Institutional empowerment is thus a crucial aspect to support inclusive and sustainable economic development.